Kitab “Barzanji” dalam Perspektif Masyarakat Muslim di Manado, Sulawesi Utara - Gayda Bahmid (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2014)
The book Barzanji is one of the Arabic oral literary genre that generally, its user community does not comprehend its meaning; however, this literary work has been integrated in the Moslem community’s thinking pattern. a number of values in the user community’s thinking pattern. This research aimed at: (1) identifying and interpreting the oral literary text in line with linguistic paradigm, (2) revealing the value phenomena originating from social, cultural, and metaphysical themes, and (3) studying the user community’s comprehension that tends to retain the primordial image in accordance with the essential belief. Qualitative descriptive method was used. The research findings indicate that the intra linguistic are closely related to the extra linguistic ones meet in social theme contain values of respect, togetherness, brotherhood and appreciation, The cultural themes bear the values of calmness, happiness, gratitude, and the metaphysical (philosophical) ones have the value of belief, faith and conviction.Keywords: Barzanji, Linguistic, Social Cultural, Metaphysical Phenomena, Moslem Perspective.